Construction of a system of flow and temperature instrumentation on a porcine farm in the municipality of Marsella, Risaralda - Henao Baena, Carlos Alberto; González Santamaría, Luis Alberto; Álvarez López, Mauricio Alexander (Scientia et Technica, 2018)
We present a local monitoring system of temperatureand caudal in a pig farm. The method consists of designing aninstrumentation and measurement system, this uses a wirelesssensor network (WSN) based on the ZigBee standard. The WSNsends the gathered data to a server that stores the information ina database with the purpose of consulting (local queries) at anytime the data that have been measured by the electronic devices.The preliminary results show that the data we can be used toinfer behavior of the variables under study, besides the prototypeis scalable, efficient, that makes it easily adaptable to any pigfarm.